2011
DOI: 10.1093/brain/awr313
|View full text |Cite
|
Sign up to set email alerts
|

Cortical activation changes underlying stimulation-induced behavioural gains in chronic stroke

Abstract: Transcranial direct current stimulation, a form of non-invasive brain stimulation, is showing increasing promise as an adjunct therapy in rehabilitation following stroke. However, although significant behavioural improvements have been reported in proof-of-principle studies, the underlying mechanisms are poorly understood. The rationale for transcranial direct current stimulation as therapy for stroke is that therapeutic stimulation paradigms increase activity in ipsilesional motor cortical areas, but this has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
151
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(169 citation statements)
references
References 28 publications
15
151
1
2
Order By: Relevance
“…After the anodal stimulation, we observed an increase in the cortical response not only over the stimulated cortex (Stagg et al, 2009a;Stagg et al, 2011) but also over the contralateral homotopic areas. This result is consistent with a recent study (Zheng et al, 2011) that reports a positive correlation between the stimulated motor cortex and the contralateral one, supporting a possible coupling of neuroactivity between motor regions (although in our study, the stimulated hemisphere was more strongly activated than the contralateral region).…”
Section: Tdcs-induced Changes In Cortical Excitabilitymentioning
confidence: 78%
“…After the anodal stimulation, we observed an increase in the cortical response not only over the stimulated cortex (Stagg et al, 2009a;Stagg et al, 2011) but also over the contralateral homotopic areas. This result is consistent with a recent study (Zheng et al, 2011) that reports a positive correlation between the stimulated motor cortex and the contralateral one, supporting a possible coupling of neuroactivity between motor regions (although in our study, the stimulated hemisphere was more strongly activated than the contralateral region).…”
Section: Tdcs-induced Changes In Cortical Excitabilitymentioning
confidence: 78%
“…Thereby, the priming activation by tDCS could have optimized the plastic effects induced by the intensive training of the paretic upper limb and lead to more remarkable clinical gains. Previous findings have demonstrated that the degree of behavioural improvement immediately following tDCS was correlated with the stimulation-induced changes in the affected hemisphere activity [42]. However, it is probable that the magnitude of the affected hemisphere activation is dependent on whether neural circuits are directly or indirectly activated.…”
Section: Discussionmentioning
confidence: 98%
“…Whether or not tDCS is able to interact at a synaptic level with endogenous plasticity-induction protocols is not only an interesting academic question but also has important implications for the use of tDCS as an adjunctive therapy in recovery of function after brain injury, such as a stroke. A single session of anodal tDCS applied to the motor cortex within the ipsilesional hemisphere has been demonstrated to improve function in the chronic stages of stroke recovery for short periods of time (Hummel et al, 2005(Hummel et al, , 2006Stagg et al, 2012). Additionally, daily applications of tDCS with the anode placed over the M1 in the ipsilesional hemisphere and the cathode placed over M1 in the contralesional hemisphere appear to induce longer-lasting behavioral improvements (Lindenberg, Renga, Zhu, Nair, & Schlaug, 2010).…”
Section: Relationship Between Tdcs and Motor Learningmentioning
confidence: 99%